The Readiness Level On Conducting Penetration Testing Among Network Admin In Kolej Poly Tech Mara - Ibrahim, Mimi Dalina (UTeM, 2016)
Nowadays, most of Malaysian cannot live without internet. Malaysia become one of the country which used internet widely. However, the number of attack, suspicious event and vulnerabilities in internet increases day by day. The network administrator have to observe and monitor the network to find the suspicious event and weakness that may occur in network under their supervision. This research focus to investigate the readiness level on conducting penetration testing among network administrator in Kolej Poly-Tech MARA (KPTM). This research aimed to investigate the factors which may contribute to the readiness on conducting penetration testing among user Information Technology (IT) focus to Network Administrator in Kolej Poly-Tech MARA (KPTM), design and develop a questionnaire that cover about factors which relate to readiness in using penetration testing and analyse the relationship between dependent and independent variable towards readiness level on using penetration testing. The selected factors which are experience, knowledge and organization was explored through literature survey and interviews with IT expert. A total of 22 respondents from different level of network administrator in KPTM around Malaysia are selected for the purpose of this study. For the analysis, one way ANOVA, Pearson Correlation Coefficient and Regression was adopted to analyse the results. The result shown that all the factors have positive linear relationship between organization, experience and knowledge. This study also provides contribution from the study, limitation of the study and recommendations for future research in penetration testing.